Інформаційні технології в сучасному світі - Баюрка, Д. С. (ХНУРЕ, 2020)
The given work is devoted to determining the place of information technologies in the modern society. The basics tages of the civilization development in connection with the accumulation of humanin formation volume in specific periods of history, from originof writing to emergence of the World Wide Web, were traced. The information explosi on provided the transition of civilization to a news tage of development, "the Information Civilization". Information has become the most important resource of modern society, and the process of its processing is seenas a technology. The latter suggests the need for the legal regulation of relation saris in gfrom the use of information resources, extensions of the irscope in the modern in formation society.
Keywords: філософія; інформаційні технології